Hubungan Antara Kompetensi Pedagogik Mahasiswa Kampus Mengajar dengan Hasil Belajar Praktik Mengajar TP FIP UNP - Maharani, Maharani; Yeni J, Fetri; Rahmi, Ulfia; Amsal, Mutiara Felicita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research was motivated by students who participated in the Teaching Campus (KM) who had not been able to master and apply pedagogic competencies properly while participating in the KM program. This study aims to determine the relationship between the pedagogic competence of teaching campus students and the learning outcomes of TP FIP UNP teaching practice. This research was conducted using a quantitative research method in the form of correlation. Where there are 31 sample students who took part in KM. The data collection technique is the learning outcomes of student teaching practice. The data analysis techniques are normality test and linearity test with product moment correlation test mode. Based on the person correlation test of variable X of 0.043, this value is between 0.00-0.19 which means that the level of closeness of the variable X with Y is very weak, the Pearson Correlation value in a negative form indicates that if the variable X increases, the Y variable decreases and indicates that the Pearson correlation relationship is not unidirectional. Therefore, it can be concluded that there is a significant relationship between pedagogic competence and the learning outcomes of KM students' teaching practice.